Design and performance of felodipine-based solid dispersions - Langham, Zoe A. (2011)
In recent years the pharmaceutical industry has seen a rise in the number of drug compounds with low aqueous solubility, and consequently poor oral bioavailablility. One potential solution to this problem is to formulate such compounds as solid dispersions, whereby the drug is dispersed in a carrier matrix in the solid state.